Practical Analysis of Multimodality Based Student Book Development to Improve English Skill of Entrepreneurship Study Program Students at Universitas Negeri Medan - Sabda Dian Nurani Siahaan; Esa Setiana; Lenti Susanna Saragih; Haryani Pratiwi Sitompul (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to produce teaching materials in the form of handbooks to improve the quality of learning in the Entrepreneurship Study Program, Universitas Negeri Medan. This study uses a 4D Model that is defined, designed, developed and disseminated. The data analysis techniques used is practicality. Practical tests were carried out on research samples, consist by 60 students of the 2nd semester entrepreneurship study program. The practicality test measured from student questionnaire obtained 90,5%, which means it is very practical.